Hot compressive deformation behavior and microstructure evolution of a Ti-55511 alloy with basket-weave microstructures. (November 2019) - Lin, Y.C.; Pang, Guo-Dong; Jiang, Yu-Qiang; Liu, Xin-Gang; Zhang, Xiao-Yong; Chen, Chao; Zhou, Ke-Chao
Abstract: The hot deformation behavior and microstructural evolution of a Ti-55511 alloy in α+β region are investigated by uniaxial compressive tests at elevated temperatures. Transmission Electron Microscope (TEM) and Electron Backscattered Diffraction (EBSD) are employed to observe the microstructures. The spheroidization of lamellate α phases and the dynamic recrystallization (DRX) of β grains are analyzed. It is observed that the flow characteristics are prominently affected by deformation parameters, i.e., the flow stress, peak stress and flow softening stress decrease with the reduced strain rate or the increased deformation temperature. When the deformation temperature is slightly raised or the strain rate is properly reduced, the fraction of spheroidized α phase greatly increases. The substructures are formed in the lamellate α phase, and the β phase wedges into the lamellate α phase. Then, the lamellate α phase is fragmentized and spheroidized. The DRX of β grains is promoted with the raised strain rate or the reduced deformation temperature. Additionally, the higher dislocation density and obvious dislocation pile-ups can be noticed at the α/β interface, which induces the DRX nucleation of β grains at the α/β interface. Highlights: Hot deformation behavior and microstructure evolution of a Ti-55511 alloy in α+β region are investigated. The fraction of spheroidized α phase increases with increasing deformation temperature or reducing strain rate. The substructures are easily formed in the lamellate α phase, and the β phase wedges into the lamellate α phase. The DRX of β grains is promoted with the raised strain rate or the reduced deformation temperature. The obvious DRX of β grains easily nucleate at the α/β interface.